2008
DOI: 10.1002/pro.6
|View full text |Cite
|
Sign up to set email alerts
|

Structural features for the mechanism of antitumor action of a dimeric human pancreatic ribonuclease variant

Abstract: A specialized class of RNases shows a high cytotoxicity toward tumor cell lines, which is critically dependent on their ability to reach the cytosol and to evade the action of the ribonuclease inhibitor (RI). The cytotoxicity and antitumor activity of bovine seminal ribonuclease (BSRNase), which exists in the native state as an equilibrium mixture of a swapped and an unswapped dimer, are peculiar properties of the swapped form. A dimeric variant (HHP2-RNase) of human pancreatic RNase, in which the enzyme has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The other two substitutions present in the hinge peptide of the seminal enzyme, E111→G and Y115→S, confer a high conformational flexibility to this region, facilitating the dissociation of the dimer in solution. All these experimental data confirm the important role that in the 3D‐DS phenomenon is played by the hinge region [4,38,39], the only structural element that in a swapping process undergoes a rather large conformational rearrangement.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The other two substitutions present in the hinge peptide of the seminal enzyme, E111→G and Y115→S, confer a high conformational flexibility to this region, facilitating the dissociation of the dimer in solution. All these experimental data confirm the important role that in the 3D‐DS phenomenon is played by the hinge region [4,38,39], the only structural element that in a swapping process undergoes a rather large conformational rearrangement.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed the rmsd between one of the two subunits and the monomeric enzyme (PDB code: http://1N1X) is ∼0.7 Å (rmsd calculated for main chain atoms of residues 1–110 and 117–124). A phosphate ion is bound to each composite catalytic site stabilizing the dimer by mimicking the enzyme substrate, as typically observed in several other ribonuclease structures [12,21,29,37,38].…”
Section: Resultsmentioning
confidence: 91%
“…40,41 PDZ domains possess similar sequence and fold. This usually consists of six b-strands (namely A-F) and two a-helices [30][31][32][33] and the following five-residue bhairpin (CDSPV) connecting strands B-C. A structural comparison with other PDZ domains sharing high-sequence identity and very similar 3D structure (i.e. pdbcode 1g9o) shows a significant difference just in this region, where other PDZ domains are glycine rich.…”
Section: Four Cysteines Ring Motif In Proteinsmentioning
confidence: 98%
“…30 This explanation of the cytotoxic activity of the swapped form of the seminal enzyme is consistent with the results of several studies carried out on ad hoc designed mutants, 24,31 of the seminal enzyme as well as on those of homologous monomeric pancreatic RNases. In particular, both bovine 32 and human 33 pancreatic RNase have been transformed into cytotoxic dimeric species by introducing the 4CR motif and other residues essential for the swapping. 32,33 Altogether, these studies have clearly demonstrated that (i) the swapped dimerization confers special properties and abilities only to the predominant native isoform M3M, 19,24,25 (ii) the 4CR moiety does not allow monomerization upon unswapping and, (iii) the domain swapping does not allow monomerization upon 4CR reduction.…”
Section: The Proteins Embodying the 4cr Motifmentioning
confidence: 99%
See 1 more Smart Citation